Are publicly funded Czech incubators effective? The comparison of performance of supported and non-supported firms. Issue 4 (8th October 2018) - Dvouletý, Ondřej; Longo, Maria Cristina; Blažková, Ivana; Lukeš, Martin; Andera, Michal
Abstract : Purpose: Even in established economies, empirical studies on the relationship between business incubation and firm performance do not show unequivocally positive results. The purpose of this paper is to contribute to this debate based on the empirical evidence from the under-researched Central and Eastern European region in which no similar study has been conducted before. Due to the shorter experience with the management of business incubators and less developed institutions, business incubators may not be so effective in supporting their tenants in this region. Design/methodology/approach: The authors utilise firm-level data from incubated Czech enterprises ( n =205) founded after 2003 and compare them with those that have not received support from incubators. The authors implement three matching techniques to pair incubated and non-incubated companies. The outcome variables measured sales, price-cost margin, assets turnover, value added, size of total assets and size of personnel costs. Findings: Compared to the control group, incubated firms reported on average lower values of the above-mentioned indicators. Presented study shows that Czech incubators have not been successful in supporting growth of incubated firms. Practical implications: The study suggests that there is a clear room for improvements. Incubators should improve in attracting and selecting high potentials and in providing more effective support focussed on tenants' growth, whereas policymakers should exercise stricter control regarding the money spent and effectiveness of incubators. Originality/value: The empirical analysis was conducted based on the research gap in the studies related to the impact of business incubation in the under-researched Central and Eastern European region. It also shows that positive results from similar studies done in established economies cannot be taken for granted as they depend on the quality of institutions in a particular country.